2020
DOI: 10.3389/fevo.2020.00075
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of a Secreted Immune Molecule Interferes With Termite Social Immunity

Abstract: Social immune behaviors are described in a great variety of insect societies and their role in preventing emerging infectious diseases has become a major topic in insect research. The social immune system consists of multiple layers, ranging from the synthesis of external immune molecules to the coordination of individual behaviors into sophisticated collective defensive tasks. But our understanding of how complex group-level behavioral defenses are orchestrated has remained limited. We sought to address this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…are widespread in non-social insect lineages (Bulmer et al, 2012;Otti et al, 2014;Meunier, 2015). Therefore, initially simple, cooperative behaviors such as grooming, combined with means to deploy disinfectants into the external environment, could both protect the group and encourage further cooperation (Esparza-Mora et al, 2020).…”
Section: Group Formationmentioning
confidence: 99%
“…are widespread in non-social insect lineages (Bulmer et al, 2012;Otti et al, 2014;Meunier, 2015). Therefore, initially simple, cooperative behaviors such as grooming, combined with means to deploy disinfectants into the external environment, could both protect the group and encourage further cooperation (Esparza-Mora et al, 2020).…”
Section: Group Formationmentioning
confidence: 99%
“…However, social and innate immunity are not independent of each other (Liu et al, 2015). Studies have confirmed that social immunity depends in part on the regulation of exogenous enzymes associated with the body's immune system (Esparza-Mora et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Immune gene components, particularly immune effectors, have been implicated in the evolution of social immunity. In termites, termicins, a defensin-like gene family, has been duplicated during the evolution of termites (Bulmer and Crozier, 2004), while gram-negative bacteria-binding proteins (GNBP) have acquired a novel fungicidal function in the common ancestor of eusocial termites and subsocial wood roaches via gene duplication (Bulmer et al, 2012), and may play a role in termite collective defensive behavior (Esparza-Mora et al, 2020). In contrast, it has also been hypothesized that sociality could lead to relaxed selection on the individual immune system, potentially via enhanced behaviourally-mediated protection (e.g.…”
Section: Introductionmentioning
confidence: 99%